BREAST CANCER IN WOMEN: CHARACTERIZATION OF CASES INCLUDED IN THE HOSPITAL CANCER RECORDS OF THE STATE OF SÃO PAULO AND FACTORS ASSOCIATED WITH ADVANCED STADIUMS - Almeida, Raissa Janine de; Decker, Arthur Felipe; Luizaga, Carolina Terra de Moraes; Murta-Nascimento, Cristiane (Mastology, 2020)
Introduction: Breast cancer is a worldwide public health problem, being the most common malignancy in the female population. It is a potentially curable disease if diagnosed early. The advanced stage at the time of diagnosis is associated with increased morbidity and low survival of these women. Objectives: To describe the sociodemographic, clinical, and anatomopathological characteristics of breast cancer cases in women included in the São Paulo State hospital cancer database (registros hospitalares de câncer de São Paulo – RHC-SP), established in 2000 and maintained by the Fundação Oncocentro de São Paulo (FOSP) and to investigate the factors associated with the clinical stage at the time of diagno-sis. Material and methods: The study design was a series of cases. The sample consisted of women with breast cancer diagnosed between 2000-2014 and included in the RHC-FOSP. The outcome variable was the clinical stage (stage 0-II ver-sus III-IV). The explanatory variables were: age at diagnosis and education level. This study was approved by the Human Research Ethics Committee of the Botucatu Medical School, UNESP. Results: The study included 84,987 women with in situ and invasive breast cancer diagnosed between 2000-2014. The mean age of women at diagnosis was 56.7 years (95%CI 56.6–56.8 years). Sixty-five percent of the cases have complete elementary school or less and the most frequent histologi-cal type was ductal carcinoma (77.2%). During the study period, there was a small decrease in the proportion of tumors in more advanced stages, from 39.8% in 2000 to 32.6% in 2014. There was a statistically significant association between the variables age at diagnosis and level of education with the clustered clinical stage of women. Women of older age and those with a higher level of education had reduced odds ratios for tumors in more advanced stages at the time of diag-nosis. Conclusion: These findings may contribute to the development of policies for the identification of breast tumors at an earlier stage.